Mechanistic Insight Into Cadmium- and Zinc-Induced Inactivation of the Candida albicans Pif1 Helicase - Zhang, Bo; Zhang, Qintao; Zhu, Xinting; Li, Dayu; Duan, Xiaolei; Jin, Jiao; Wang, Kejia; Xie, Yan; Liu, Yang (Frontiers in Molecular Biosciences, 2022)
Zinc and cadmium are environmental contaminants that can cause disease by affecting the activity of DNA-repair proteins. In this study, we investigated the effect of Zn2+ and Cd2+ on the Candida albicans Pif1, a DNA-repair helicase that plays a critical role in ensuring genomic stability. We show that zinc and cadmium strongly inhibit both the ATPase and the unwinding activities of CaPif1, but have no effect on its DNA binding activity. High concentrations of cadmium may bind to the cysteine residues of Pif1, and its inhibition appears to be difficult to be restored by ethylene diamine tetraacetic acid, while inhibition due to Zn2+ can. When the two ions are at low concentrations, increasing the concentration of ATP in the reaction can appropriately weaken the inhibitory effect of Zn2+, while cysteine can reduce the inhibitory effect of Cd2+. In addition, we found that for both Cd2+ and Zn2+ the inhibition effects were nearly 100 times greater in reduced environments than in non-reducing environments. When heavy metals stimulate the body's response, the environment of the body becomes less reducing, and thus the tolerance of CaPif1 to heavy metals will be stronger. We propose that CaPif1 may resist the toxicity of heavy metals through this mechanism. Altogether, our results provide new insights into the mechanisms by which heavy metals are toxic to DNA-repair proteins.